2023
DOI: 10.1002/epi4.12817
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between telomere length and epilepsy: A bidirectional Mendelian randomization study

Xinxin Luo,
Zhichao Ruan,
Ling Liu

Abstract: ObjectiveObservational studies have suggested a link between telomere length (TL) and epilepsy, but the direction of the effect and whether it is causal or not is still being debated. The objective of this study was to investigate the causal relationship between TL and epilepsy using Mendelian randomization (MR) analysis.MethodsWe performed a bidirectional two‐sample MR analysis using pooled statistics from genome‐wide association studies (GWAS) of TL and epilepsy. Additionally, we conducted a replication anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Few opportunities exist to obtain brain tissue from living subjects, so all samples in this study were collected from individuals with medically intractable epilepsy which is another limitation to generalizability. There are mixed results previously on the association of peripheral TL with epilepsy: one study found increased telomere shortening in patients with drug-resistant epilepsy (Miranda et al, 2020 ) and another study identified no TL differences in individuals with epilepsy (Luo et al, 2023 ). Another study shows that individuals with the rare disorder, Revesz syndrome, that often experience seizures display decreased ability of the shelterin complex to protect telomeres from shortening (Karremann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few opportunities exist to obtain brain tissue from living subjects, so all samples in this study were collected from individuals with medically intractable epilepsy which is another limitation to generalizability. There are mixed results previously on the association of peripheral TL with epilepsy: one study found increased telomere shortening in patients with drug-resistant epilepsy (Miranda et al, 2020 ) and another study identified no TL differences in individuals with epilepsy (Luo et al, 2023 ). Another study shows that individuals with the rare disorder, Revesz syndrome, that often experience seizures display decreased ability of the shelterin complex to protect telomeres from shortening (Karremann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%